Amino Acid Transport into Human Platelets and Subsequent Incorporation into Protein - Cooper, I. A; Firkin, B. G (Thrombosis and Haemostasis, 1970)
Human platelets are known to contain various protein components. Among them are fibrinogen and other soluble proteins. The origin of such proteins has not been clear.Studies were designed to demonstrate the ability of the platelet to incorporate amino acids and subsequently utilise these for de novo protein synthesis.Seven different 14C labelled amino acids were used, cysteine, lysine, serine, glutamic acid, proline, valine und leucine.Active incorporation into platelets of all these amino acids was demonstrated with some evidence for incorporation of cysteine, lysine and serine into the fibrinogen and soluble protein.